DINAMIKA PSIKOLOGIS PADA PELAKU PEMBUNUHAN DENGAN KORBAN LEBIH DARI SATU ORANG : STUDI KASUS DUA PELAKU - Julia Vita Lyta Magdalena Muklim; Aloysius Lukas S Soesilo (Psycho Idea, 2018)
The act of murder is a crime that is considered the most troubling for the society. Murder can be grounded by a variety of causes and are influenced by a various factors. The purpose of this study is to describe every events that happened before the moment of murder, identify the condition of the subject while commiting murder and also describes the mental process of the subject after commiting the murder. This study uses case study method on two participants which a multiple murderers. The results of this study are both participants committed an act of murder influenced by various factors such as the relationship between the participants and his father, past experiences related to violence, impulsive action, self-defense that led to the killing. In addition, after the murder there is also a feeling of confusion, fear and the shadow of guilt experienced by participants. Keyword : Psychological Dynamics, Murder, Case